Rancangan Standar Operasional Prosedur (SOP) Make Up Room Kaniak Homestay Syariah di Nagari Tarantang Kecamatan Harau - Hanifa, Zahratul; Suyuthie, Hijriyantomi (Lembaga Yasin AlSys, 2023)
The problem raised in this final project is the absence of Standard Operating Procedures for Make Up Rooms at Kaniak Homestay Syariah. The purpose of this final project is to design Standard Operating Procedures for Make Up so that it can anticipate, minimize and even eliminate risks that might occur, such as complaints from guests that can affect the image of the homestay. The method used in this final project is descriptive method with qualitative data. The results of the draft Standard Operating Procedures for Make Up Rooms are activities of entering rooms, starting tasks, picking up trash, making beds, cleaning dust, cleaning bedrooms, sweeping and mopping, inspecting guest rooms which are carried out in a structured manner in approximately 15 minutes.